Increased HBV Coinfection and Decreased IFN-γ-Producing HBV-Specific CD8+ T Cell Numbers During HIV Disease Progression - Zhu, Zhiqiang; Qin, Yuanyuan; Liang, Qi; Xia, Wei; Zhang, Tong; Wang, Wen; Zhang, Mengmeng; Jiang, Taiyi; Wu, Hao; Tian, Ye (Frontiers in Immunology, 2022)
Objective: To investigate the characteristics and mechanism of the dynamics of HBV infection with the progression of HIV disease and to explore the different responses of T lymphocytes to HBV in HIV patients in different stages of disease. Methods: We compared the rates and characteristics of HBV coinfection between 372 early HIV-infected and 306 chronically HIV-infected men who have sex with men (MSM) in the Beijing Youan Hospital from October 2006 to November 2014. We further analysed IFN-γ producing HBV-specific CD8+ T cells in 15 early HIV-infected individuals and 20 chronic HIV-infected individuals with HBV coinfection. Results: Twenty-three HBsAg-positive cases were detected among the 372 early HIV-infected patients of this cohort, and the coinfection rate was 6.18%, while 35 HBsAg-positive cases were detected among the 306 chronically HIV-infected patients, with a coinfection rate of 11.44%. The coinfection rate of the chronically HIV-infected patients was significantly higher than that of the early-infected patients (p=0.0005). The median CD4+ T cell count in the early HIV infection patients was 445 cells/μL (196-1,030 cells/μL), which was higher than that in the chronic HIV infection patients (358 cells/μL (17-783 cells/μL)) (p<0.001). The proportion of IFN-γ producing CD8+ T cells in early HIV-infected patients was significantly higher than that in chronically HIV-infected patients. Conclusion: The coinfection rate of HBV in HIV patients increases with HIV disease progression, which might be related to the decreased IFN-γ-producing HBV-specific CD8+ T cell numbers. The closely monitored HBV serum markers from the early stage of HIV infection are warranted.